Cases and distribution of visceral leishmaniasis in western são paulo: A neglected disease in this region of Brazil - Soares Santana, Regiane; Briguenti Souza, Karina; Lussari, Fernanda; Fonsecaid, Elivelton Silva; Andrade, Cristiane Oliveira; Meidas, Marcia Mitiko Kaihara; D’andrea, Lourdes Aparecida Zampieri; Silva, Francisco Assis; Flores, Edilson Ferreira [UNESP]; Anjolete, Ivete Rocha; Prestes-Carneiroid, Luiz Euribel (Public Library of Science (PLoS), 2021)
Visceral leishmaniasis (VL) is one of the most prevalent parasitic diseases worldwide. In 2019, 97% of the total numbers of cases in Latin America were reported in Brazil. In São Paulo state, currently 17.6% of infected individuals live in the western region. To study this neglected disease on a regional scale, we describe the spread of VL in 45 municipalities of the Regional Network for Health Assistance11(RNHA11). Environmental, human VL (HVL), and canine VL (CVL) cases, Human Development Index, and Lutzomyia longipalpis data-bases were obtained from public agencies. Global Moran’s I index and local indicators of spatial association (LISA) statistics were used to identify spatial autocorrelation and to gen-erate maps for the identification of VL clusters. On a local scale, we determined the spread of VL in the city of Teodoro Sampaio, part of the Pontal of Paranapanema. In Teodoro Sam-paio, monthly peri-domicile sand fly collection; ELISA, IFAT and Rapid Test serological CVL; and ELISA HVL serum surveys were carried out. In RNHA11 from 2000 to 2018, Lu. longipalpis was found in 77.8%, CVL in 69%, and HVL in 42.2% of the 45 municipalities, and 537 individuals were notified with HVL. Dispersion occurred from the epicenter in the north to Teodoro Sampaio, in the south, where Lu. longipalpis and CVL were found in 2010, HVL in 2018, and critical hotspots of CVL were found in the periphery. Moran’s Global Index showed a weak but statistically significant spatial autocorrelation related to cases of CVL (I = 0.2572), and 11 municipalities were identified as priority areas for implementing surveillance and control actions. In RNHA11, a complex array of socioeconomic and environmental factors may be fueling the epidemic and sustaining endemic transmission of VL, adding to the study of a neglected disease in a region of São Paulo, Brazil.